The Effect of Abdominal Effleurage Massage on Reducing Primary Dysmenore in Adolescents - Hasanah Hasanah; Sri Kustiyati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Background: Primary dysmenorrhea is abdominal pain, cramps and back pain experienced by women at the beginning of menstruation for 48-72 hours. This condition is most often experienced by women in their late teens to young adults (15-25 years) due to optimization of uterine function so that prostaglandin secretion increases. In Indonesia, the prevalence of primary dysmenorrhea reaches 54.89%, with a significant impact on adolescent activities. One of the effective non-pharmacological methods to overcome primary dysmenorrhea is abdominal effleurage massage, which is performed directly on the site of pain so that endogenous analgesics (endorphins) are released and pain transmission to the cerebral cortex is inhibited. Purposes: To analyze the effect of abdominal effleurage massage on reducing primary dysmenorrhea in adolescents. Research method: This study used a quantitative method with a pre-experimental one group pretest posttest design method. The population of this study was 45 adolescents. The sample was taken using a simple random sampling technique of 21 female students who experienced primary dysmenorrhea. Data collection was carried out using the NRS (Numeric Rating Scale) pain scale observation sheet. Data were analyzed using the Wilcoxon Signed Rank Test. Results: Based on the analysis test using the Wilcoxon Signed Rank Test, a significance value of 0.00 (p <0.05) was obtained, which means Ha was accepted. In other words, abdominal effleurage massage has an effect on reducing primary dysmenorrhea in adolescents. Conclusion: There is an effect of abdominal effleurage massage on reducing primary dysmenorrhea in adolescents.